Extractive separation of benzene and cyclohexane using binary mixtures of ionic liquids - Salleh, M. Zulhaziman M.; Hadj-Kali, M.K.; Wazeer, Irfan; Ali, Emad; Hashim, Mohd Ali (Elsevier, 2019)
The separation of benzene and cyclohexane is a challenging process in petrochemical industry due to their close boiling points. Solvent mixing is a useful technique to enhance the extraction performance of liquid–liquid extraction process. In this work, the performance of solvent mixtures involving two organic solvents (N,N-dimethylformamide and ethylene glycol) and four ionic liquids (ILs), namely, 1-ethyl-3-methylimidazolium thiocyanate (C2mimSCN), 1-ethyl-3-methylimidazolium dicyanamide (C2mimN(CN)2), 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (C2mimTf2N) and 1-ethyl-3-methylimidazolium acetate (C2mimAc) was investigated for the extractive separation of benzene and cyclohexane. The mixing ratios of the binary solvents were optimized using the ideal mixing calculation and validated experimentally through liquid–liquid extraction process. Six new quaternary liquid–liquid equilibria for the mixed solvents with benzene and cyclohexane were investigated at 25 °C and 1 atm, with feed concentrations of benzene ranging from 10 to 50 wt%. Ethylene glycol was discovered a good solvent pair with C2mimTf2N that could lead to potential cost savings. At the optimized mixing fraction, the {C2mimTf2N + C2mimSCN} mixture demonstrated the highest extraction performance, which was superior to that of sulfolane. Additionally, the {C2mimSCN + C2mimN(CN)2} and {C2mimN(CN)2 + C2mimAc} mixtures were found to increase the selectivity while maintaining the benzene distribution ratio in relation to sulfolane. The ILs were not present in the raffinate layer of any of the systems, indicating the reliable performance of the ILs in terms of avoiding solvent cross-contamination. This work demonstrated the use of binary solvent mixtures as a new efficient and versatile method to enhance extraction performance. © 2019 Elsevier B.V.